Pengaruh Lingkungan Eksternal, Lingkungan Internal, Strategi Kepemimpinan Biaya, Strategi Diferensiasi, Terhadap Nilai Pelanggan, dan Keunggulan Bersaing - Ingga, Ibrahim (Universitas Brawijaya, Indonesia, 2009)
The objectives of this research is to know: (1) The impact of external and internal environment on the low cost strategy, differentiation strategy, and competitive advantage. (2) The impact of low cost strategy and differentiation strategy on the customer value and competitive advantage. (3) The impact of customer value on competitive advantage. The population of this research are consist of 150 industries manufacture which have Go Public at Bursa Effect Jakarta. Its research's sampling are 125 industries manufacture. The data collected were questionnaires and interview. The method analysis used was structural equation modeling (SEM). The result of this research shows that: (1) The external environment variable has a positively and significantly influence on the low cost strategy and differentiation strategy, but has not significantly influence on competitive advantage. (2) The internal variable has a positively and significantly on the low cost strategy, but has not significantly influence on the differentiation strategy and the competitive advantage. (3) The low cost strategy variable has a positively and significantly on the customer value variable and competitive advantage variable. (4) The differentiation variable has not significantly influence on the customer value variable and competitive advantage variable. (5). The customer value variable has not significantly influence on the competitive advantage.